Pemeriksaan Bakteriologis Escherichia Coli Pada Sampel Air Minum Rumah Tangga Di Kecamatan Lawe Sumur Kabupaten Aceh Tenggara Tahun 2026 - Siska Putri Belangi; Inneke Mutiara Amelia; Mutiara Hikmah; Khalikul Fadli; Nur Triningtias P (Indonesian Journal of Innovation Multidisipliner Research, 2026)
Safe drinking water is a basic necessity and must meet health requirements, including being free from bacteriological contamination such as Escherichia coli. This study aimed to determine the bacteriological quality of household drinking water in Lawe Sumur District, Southeast Aceh Regency in 2026. This research used a descriptive design with a laboratory survey approach. A total of 30 household drinking water samples were collected from three selected villages: Lawe Sumur Village, Kute Bunin Village, and Terutung Megara Baru Village, with 10 samples from each village. Bacteriological examination was conducted using the Sanitarian Kit method to detect the presence of E. coli. The results showed that out of 30 samples, 19 samples (63.3%) met the requirements (MS) or were negative for E. coli, while 11 samples (36.7%) did not meet the requirements (TMS) or were positive for E. coli. In Lawe Sumur Village, 8 samples (80%) met the requirements and 2 samples (20%) did not. In Kute Bunin Village, 6 samples (60%) met the requirements and 4 samples (40%) did not. In Terutung Megara Baru Village, 5 samples (50%) met the requirements and 5 samples (50%) did not. The study concludes that bacteriological contamination still exists in household drinking water in Lawe Sumur District. Therefore, improved monitoring and public education on safe drinking water management are necessary.